Reformasi Hukum Mengenai Kewajiban Mediasi Sebagai Penyelesaian Sengketa Paten - Anugrah Pratama; Zainal Arifin Hoesein (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study analyzes the ambiguity regarding the obligation to mediate in resolving patent disputes according to the Patent Law, and its implications for the efficiency of the dispute resolution process. Although Article 153 and Article 154 of the Patent Law open up opportunities for dispute resolution through alternative mechanisms, the ambiguity regarding the obligation to mediate creates legal uncertainty that can hinder efficiency and increase dispute costs. Based on the Economic Analysis of Law approach, this study shows that the obligation to mediate can reduce social costs, accelerate the dispute resolution process, and increase overall economic efficiency. Mediation as an obligation can reduce the burden on the judicial system, minimize transaction costs, and create better legal and business stability. Therefore, this study encourages the implementation of the obligation to mediate in patent disputes to create a more efficient, fair, and profitable dispute resolution system for all parties involved.